Safety I to Safety II: A Paradigm Shift or More Work as Imagined? Comment on "False Dawns and New Horizons in Patient Safety Research and Practice" - Smith, Kelly M.; Valenta, Annette L. (International journal of health policy and management, 2018)
In their editorial, Mannion and Braithwaite contend that the approach to solving the problem of unsafe care, Safety I, is flawed and requires a shift in thinking to what they are calling Safety II. We have reservations as to whether by itself the shift from Safety I to Safety II is sufficient. Perhaps our failure to improve outcomes in the field of patient safety and quality lies less in our approach - Safety I vs. Safety II - and more in the lack of an agreed upon, commonly understood set of core competencies (knowledge, skills, and attitudes) needed in its workforce. The authors explore in this commentary the need to establish core competencies as part of the pathway to professionalism for the discipline of patient safety and quality.